Pollutants in the South Atlantic Ocean: Sources, Knowledge Gaps and Perspectives for the Decade of Ocean Science - Hatje, Vanessa; Andrade, Raiza L. B.; Oliveira, Carina Costa de; Polejack, Andrei; Gxaba, Thandiwe (Frontiers in Marine Science, 2021)
The current manuscript presents the main issues related to the “Clean Ocean” outcome that arose from the Regional South Atlantic (SA) Planning Workshop for the UN Decade of Ocean Science and five Brazilian Regional Planning Workshops. An interdisciplinary and trans-sectoral group constituted by the academia, non-governmental agencies, the private sector, decision-makers, the navy, and local communities discussed the main anthropogenic drivers compromising the current environmental status of the SA and its ecological services, and debated the main research gaps, priorities and needs for improving technical and structural capacities in order to roadmap the Brazilian actions for the Decade of Ocean Science. The aim of this review is to contribute to a social solution-driven understanding of the ocean ecosystems, to create conditions to promote sustainable development and to secure a clean, healthy ocean. We are proposing a list of actions to be implemented by the Decade of Ocean Science that will have the pivotal role to promote technical and scientific capacity development, increase research infrastructure and institutional frameworks, develop national public policies aimed at reducing the input of pollutants and management of impacts, and warranting food security and ecosystem health. The earlier the actions in controlling pollutants are implemented, along with the identification of key sources and prevention of crossing of thresholds will help to avert worst-case scenarios, reducing the socio-economic disparities of impacts across nations and social groups and supporting the sustainable development of a pollutant-free ocean.